2022
DOI: 10.3390/e24020205
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics Irreversibilities Analysis of Oxy-Fuel Diffusion Flames: The Effect of Oxygen Concentration

Abstract: In studies on the combustion process, thermodynamic analysis can be used to evaluate the irreversibility of the combustion process and improve energy utilization efficiency. In this paper, the combustion process of a laminar oxy-fuel diffusion flame was simulated, and the entropy generation due to the irreversibilities of the radiation process, the heat conduction and heat convection process, the mass diffusion process, and the chemical reaction process was calculated. The effect of the oxygen concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…It is obvious that this analytical method is better suited to the practical industrial furnace situation. Therefore, this approach was applied to various problems of thermodynamic analysis of high-temperature systems including 1-D high-temperature systems with participating medium including CO 2 , H 2 O, even soot [ 14 , 15 ], lab-scale hydrocarbon diffusion flames [ 16 , 17 , 18 ], as well as practical combustion facilities [ 19 , 20 , 21 ]. During the above studies, it was found that the thermodynamic role of thermal radiation in the combusting flows should be paid more attention, and the variation in temperature and radiative properties in combustion chambers would have crucial effects on REG.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that this analytical method is better suited to the practical industrial furnace situation. Therefore, this approach was applied to various problems of thermodynamic analysis of high-temperature systems including 1-D high-temperature systems with participating medium including CO 2 , H 2 O, even soot [ 14 , 15 ], lab-scale hydrocarbon diffusion flames [ 16 , 17 , 18 ], as well as practical combustion facilities [ 19 , 20 , 21 ]. During the above studies, it was found that the thermodynamic role of thermal radiation in the combusting flows should be paid more attention, and the variation in temperature and radiative properties in combustion chambers would have crucial effects on REG.…”
Section: Introductionmentioning
confidence: 99%
“…Datta [ 17 , 18 ] calculated the entropy generation in a laminar jet diffusion flame, and he analyzed the effect of gravity on the rate of entropy generation. Meanwhile, Lou et al [ 19 , 20 , 21 , 22 , 23 ] calculated the radiative entropy generation in flames, and they also investigated the effects of soot and temperature on entropy generation in hydrocarbon flames. Recently, the thermodynamics second-law analysis of the combustion process of hydrogen has received extensive attention.…”
Section: Introductionmentioning
confidence: 99%